Sand Flies of the Subgenus Adlerius (Diptera: Psychodidae) in an Endemic Focus of Visceral Leishmaniasis and Introduction of Phlebotomus (Adlerius) comatus as a New Record for Iran. - Ali Reza Zahraei-Ramazani; Dinesh Kumar; MohammadReza Yaghoobi-Ershadi; Abdollah Naghian; Reza Jafari; Mohammad Reza Shirzadi; Hamid Abdoli; Hassan Soleimani; Niloofar Shareghi; Maryam Ghanei; Mohammad Hossein Arandian; AhmadAli Hanafi-Bojd (Tehran University of Medical Sciences, 2013)
Background: Sand flies of subgenus Adlerius has a wide geographical distribution in Iran and are mostly found in wild form in mountainous areas. They are always considered as probable vectors of visceral leishmaniasis. The ob- jective of this study was to determine the Adlerius species and its composition in an endemic focus of zoonotic vis- ceral leishmaniasis in northwest of the country. Methods: Sand flies were collected from 6 different areas of Azarbaijan-e-Sharqi Province using sticky paper traps from August to September which is active season for sand flies in this area, in 2009. The flies were mounted and identified. The length of third antennal segments, ascoid, labrum, coxite, surstyle, style, aedeagus, genital filament, genital pump, width of style, and the end of aedeagus were measured and the number of costal hairs group was also counted as the morphological characters. Results: A total of 30 adult sand flies, (26 males and 4 females) including Phlebotomus halepensis (46.8%), P. longiductus (13.3%), P. balcanicus (23.3%), P. comatus (3.3%), and Adlerius spp. (13.3%) belong to subgenus Adlerius were identified respectively in 6 counties. One P. comatus male was captured in front of a cave located in the hillside of a mountain covered with the vegetation in Varzeqan area. Conclusion: The presence of at least 5 species of the subgenus Adlerius in Azarbaijan-e-Sharqi Province, an en- demic focus of zoonotic visceral leishmaniasis in Iran, shows that the risk of parasite transmission among man and reservoir animals is high during the active season of sand flies. P. comatus is a new record for Iran and needs to be added to the list of Iranian phlebotomines of subgenus Adlerius.